Pengolahan Citra Digital Untuk Pengukuran Morfometrik Pada Sapi Potong Lokal Berbasis Android - Fajar Ariadi; Bambang Minto Basuki, S.T., M.T.; M Jasa Afroni, S.T., M.T., Ph.D (SCIENCE ELECTRO, 2022)
Cattle farmers, especially local beef cattle in Indonesia, generally determine the price through bargaining between the seller and the buyer and the interaction between supply and demand is not based on the body weight of the cattle to be sold. The reality in the field shows that to get the value of chest circumference and body length, manual measurements need to be carried out, and this is not easy to do because cows are difficult to condition. Therefore, a tool is needed for morphometric measurements of livestock with an easier method, which can minimize the risk of stress livestock during measurement and the risk of livestock attacks that can injure researchers.As a solution for more effective morphometric measurements is digital imaging using Android-based edge detection. The digital imaging process uses the OpenCV library to detect cow objects.result of this study indicate that the implementation of image processing to produce morphometric determinations in the form of chest circumference and body length obtained an average error of 11.05% for chest circumference and 9.91% for body length. So that level of accuracy of morphometric chest circumference and body length obtained 88.95% for chest circumference and 90.09% for body length.